Pathophysiological Role and Therapeutic Implications of Vitamin D in Autoimmunity: Focus on Chronic Autoimmune Diseases - Bellan, Mattia (Nutrients, 2020)
Vitamin D is a pleiotropic secosteroid yielding multiple actions in human physiology. Besides the canonical regulatory activity on bone metabolism, several non-classical actions have been described and the ability of vitamin D to partake in the regulation of the immune system is particularly interesting, though far stronger and convincing evidence has been collected in in vitro as compared to in vivo studies. Whether vitamin D is able to regulate at physiological concentrations the human immune system remains unproven to date. Consequently, it is not established if vitamin D status is a factor involved in the pathogenesis of immune-mediated diseases and if cholecalciferol supplementation acts as an adjuvant for autoimmune diseases. The development of autoimmunity is a heterogeneous process, which may involve different organs and systems with a wide range of clinical implications. In the present paper, we reviewed the current evidences regarding vitamin D role in the pathogenesis and management of different autoimmune diseases.